If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(d + 3) + 2 = 10 Reorder the terms: 4(3 + d) + 2 = 10 (3 * 4 + d * 4) + 2 = 10 (12 + 4d) + 2 = 10 Reorder the terms: 12 + 2 + 4d = 10 Combine like terms: 12 + 2 = 14 14 + 4d = 10 Solving 14 + 4d = 10 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 4d = 10 + -14 Combine like terms: 14 + -14 = 0 0 + 4d = 10 + -14 4d = 10 + -14 Combine like terms: 10 + -14 = -4 4d = -4 Divide each side by '4'. d = -1 Simplifying d = -1
| 3(d-12)=d+24 | | 9b+10=1 | | 2p+8=6 | | 3x+26=x+4 | | 20+8=6 | | 2x-4x^2= | | 16-3t=-7t | | 18-5(x+1)=3(x-1) | | 10g-47-4g=16+3g | | 8x^3-6x+1=0 | | 22-4x=2x-4 | | w-5+3w=6w-1 | | 10c+5=4c-1 | | 3x+3=4x-6 | | 7(x-10)=21 | | 14*(2x+2)=1716+6*(x+2) | | x^2+6x+8=e^2 | | z^2+iz=0 | | 3.3x=6.5(10x+4) | | ln(2x^2+7x-4)=2+ln(x^2+x-12) | | -1+(2t+3)+2(t-3)= | | 7x+5=45+3x | | ln(x)+ln(x-3)=ln(40) | | 6(p-5)-(4p+9)=25 | | 11a+18b+6C+4C-4B-2A= | | 8x+17=25 | | 15-(y+6)=16 | | 2(4a+2)-3(2a-4)= | | -3(x-5)+2(4x-8)=12 | | 2x^2+3x=200 | | 0.5x^2+3x-36=0 | | 2xy-5yx+7= |